Pornography and Sexual Crimes towards Children in Indonesia: A Judicial Approach - Sulistyo, Faizin; Manap, Nazura Abdul (Brawijaya Law Journal, 2018)
Pornography and sexual crimes against children are two forms of crime in Indonesia. Both of these crimes in various cases have a linkage with each other, whether one of which is a crime or pornography becomes a criminogenic factor for the onset of sexual crimes against children. The review in this article attempts to look at the approach used by judges in deciding cases of sexual crimes against children that correlate with pornographic crimes. This research employs normative juridical research using legislation and case approach.The results of the review found that, in sum, there are two model of approach used by the Court in deciding criminal cases, especially pornography related to sexual crimes, which include the approach in understanding and assesing cases; and theories of punishment approach. While the rfirst model of approach emphasizes on the understanding the impact of the action, the secodn model look more at the retaliation, prevention, combination and contemporary approach. It is further argued that those two models are not necessarily used separately. The combination of the two models can also be employed, such as in the case of Tanjung Pati District Court's Ruling no. 58 /Pid.B/ 2011 /PN.Tjp. In fact, in the case, the judges combine several approaches in deciding cases and punishing defendants. It is submitted that the objective of a judge is crucial since the objectivity resulted in a fairer verdict for the victim, the community or the perpetrator himself.